Effect of Debye Plasma on Hydrogenic Photoionization Cross Section - Das, Madhusmita; Gupta, N. K. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
In this work, we have studied the effect of plasma screening on the ground and excited state photoionization cross section \((σ)\) of hydrogenic system. We have considered weakly coupled plasma where the screening of nuclear charge by plasma free electrons is represented by Debye-Huckel potential. Using this potential, radial Schrodinger equation is solved numerically to obtain the bound and free state wave functions, and transition matrix elements. Adaptive step size controlled Runge-Kutta method is used for numerical integration. Use of adaptive method for grid generation ensures lesser computational time as compared to uniform grid system. Using the methodology, we have computed photoionization cross section from \(1s\) ground state and excited \(2p\) state of hydrogenic system. Strong enhancements in \(σ\) are observed which are generally termed as shape resonances. It is noted that these resonances occur for specific screening values where bound states are pressure ionized to enter the quasi-bound regime. The changes in the phase and amplitude of continuum wave functions also lead to appearance of Cooper minimum in \(σ\) of excited \(2s\) state. We have compared the results with existing theoretical and experimental data wherever they are available.